Diversity and spatial distribution of Wolbachia infection and its association with mitochondrial DNA variation in the freshwater bug Aphelocheirus aestivalis (Insecta: Heteroptera) - Agnieszka Kaczmarczyk-Ziemba; Dariusz Halabowski; Tomasz Rewicz; Tomasz Krepski; Gavril Marius Berchi; Pál Boda; Desislava Stoianova; Giedrė Višinskienė; Michael J. Raupach (Hydrobiologia, 2026)
Wolbachia is a widespread maternally inherited endosymbiont of arthropods that can alter host reproduction, population structure, and genetic diversity. However, its prevalence and evolutionary effects in aquatic insects remain poorly understood. Here, we investigated the prevalence, spatial distribution, and genetic diversity of Wolbachia infecting the freshwater bug Aphelocheirus aestivalis across Europe and assessed its potential influence on host mitochondrial and nuclear genetic variation. Individuals from 63 populations were screened using the wsp marker. Infection occurred in 76% of populations, ranging from 0 to 100%, with an average of 42.1% individuals infected. Frequency differed between life stages, with adults more often infected than juveniles, but showed no association with sex or geography. Phylogenetic analyses revealed two divergent subgroups within supergroup A, with overlapping distributions and co-infections in central Europe. Host diversity was assessed using mitochondrial and nuclear markers. Mitochondrial data showed heteroplasmy, low nucleotide diversity, and dominant haplotypes, while nuclear variation was limited. Infected individuals had reduced mitochondrial nucleotide diversity, though haplotype diversity remained moderate. Neutrality tests indicated excess rare haplotypes, with no significant association between host haplotypes and Wolbachia groups. Results suggest Wolbachia is widespread but heterogeneous in A. aestivalis and may influence mitochondrial diversity through demographic or selective processes.